Risk factors associated with Urinary Tract Infection (UTI) in women: an integrative literature review (Research, Society and Development, 2021)
Introduction: the urinary system is responsible for removing the end products of metabolism and regulating body fluids. Urinary tract infections (UTI) are recurrent complaints, mainly affecting women and their risk factors are anatomical issues, poor hygiene, age, sexual relations and lifestyle habits. Objective: to show the main risk factors related to urinary tract infections in women. Methodology: This is a descriptive research of the integrative literature review type to identify the risk factors for urinary tract infections in women. The search was online in several databases such as PubMed MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO. The main inclusion criterion was the period 2015-2021 and with the descriptors 23 articles were found. Results and discussion: Urinary tract infection (UTI) is the invasion of microorganisms in the urinary system, which causes local inflammation. Among the main characteristics of the higher incidence in women are anatomical factors such as the proximity of the urinary tract to the perianal region and the length of the urethra. Other factors are related to hormones, hygienic evacuation and sexual habits, and environmental aspects. Conclusion: Therefore, women do have a higher prevalence, which is why it is important to adopt preventive measures and educational actions in order to ensure prophylactic behavioral modification, including hygiene, water intake and food, in order to avoid impacts and the consequent reduction in quality.